2017
DOI: 10.4028/www.scientific.net/jbbbe.32.82
|View full text |Cite
|
Sign up to set email alerts
|

Composite of Chitosan-Collagen-<i>Aloe vera</i> for Scaffolds Application on Skin Tissue

Abstract: In case of burns, scaffolds serve as cover for burns and facilitate cells regeneration. Accordingly, this study seeks procedures to synthesize composite scaffolds for burns utilizing collagen-chitosan-Aloe vera to find the best concentration of Aloe vera as scaffolds application. The synthesis of scaffolds was performed with collagen constituent composition as follow: chitosan (1:1) was dissolved in 0.05M Acetic Acid, then subsequent variations of Aloe vera (AV), namely 0% AV; 0.1% AV; 0.15% AV; 0.2% AV; and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Because each scaffold application requires a different mechanical property, different tests are used. A scaffold that is applied to the skin requires a tensile test [35]. The tensile test analysis included three aspects: tensile strength, tensile strain, and tensile stiffness.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Because each scaffold application requires a different mechanical property, different tests are used. A scaffold that is applied to the skin requires a tensile test [35]. The tensile test analysis included three aspects: tensile strength, tensile strain, and tensile stiffness.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Isfandiary et al [247] fabricated collagen-chitosan-AV composite scaffolds by a freeze drying method for healing burned skin tissue. The preparation of scaffolds was carried out by dissolving collagen-chitosan (1:1) in 0.05 M acetic acid; then, consequent variants of AV (0%, 0.1%, 0.15%, 0.2%, and 0.25%) were added into solution.…”
Section: Plant Protein-based Green Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…The preparation of scaffolds was carried out by dissolving collagen-chitosan (1:1) in 0.05 M acetic acid; then, consequent variants of AV (0%, 0.1%, 0.15%, 0.2%, and 0.25%) were added into solution. Results showed that a composite with 0.2% AV was a strong potential candidate to serve as improved scaffolds for burned skin tissue applications [247].…”
Section: Plant Protein-based Green Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…Experimental results, using cell viability assay and cell attachment observation, showed that the nano-fibrous membranes support 3T3 cell viability and could be a potential candidate for GTR therapy. Isfandiary et al [26] sought the procedures to synthesize composite scaffolds for burns utilizing collagen-chitosan-AV to find the best concentration of AV as scaffolds application. The synthesis of scaffolds was performed with collagen constituent composition as follow: collagen-chitosan (1:1) was dissolved in 0.05M acetic acid, then subsequent variations of AV, namely 0% AV, 0.1% AV, 0.15% AV, 0.2% AV, and 0.25% AV were added into collagen-chitosan solution, and freeze dry method was applied.…”
Section: Aloe Vera Gel Scaffolds With Semi-synthetic or Natural (Curcmentioning
confidence: 99%